Toward Practical All-solid-state Batteries with Sulfide Electrolyte: A Review - Yuan, Hong; Liu, Jia; Lu, Yang; Zhao, Chenzi; Cheng, Xinbing; Nan, Haoxiong; Liu, Quanbing; Huang, Jiaqi; Zhang, Qiang (Chemical research in Chinese universities, 2020)
Sulfide-based solid-state electrolytes with ultrahigh lithium ion conductivities have been considered as the most promising electrolyte system to enable practical all-solid-state batteries. However, the practical applications of the sulfide-based all-solid-state batteries are hindered by severe interfacial issues as well as large-scale material preparation and battery fabrication problems. Liquid-involved interfacial treatments and preparation processes compatible with current battery manufacturing capable of improving electrode/electrolyte interface contacts and realizing the mass production of sulfide electrolytes and the scalable fabrication of sulfide-based battery component have attracted considerable attention. In this perspective, the current advances in liquid-involved treatments and processes in sulfide-based all-solid-state batteries are summarized. Then relative chemical mechanisms and existing challenges are included. Finally, future guidance is also proposed for sulfide-based batteries. Focusing on the sulfide-based all-solid-state batteries, we aim at providing a fresh insight on understandings towards liquid-involved processes and promoting the development of all-solid-state batteries with higher energy density and better safety.